2021
DOI: 10.1080/19475705.2021.1987341
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the permeability and seepage characteristics of bimsoils

Abstract: Bimsoils are a loose rock and soil system, and the occurrence of geological hazards is closely related to water. To investigate the permeability and seepage characteristics of bimsoils, factors on permeability are discussed in detail considering cementation state, and variable mass seepage is studied tentatively with selfdeveloped apparatus. Results shown that the order of factors on permeability is rock content > cementation degree > rock size > Talbot index (describing the mass percentage for different parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Zhou et al (2017) used the constant head permeability experiment to study the seepage characteristics of bimrocks, and presented a theoretical model for the hydraulic conductivity of bimrocks. Wang et al (2021) used the constant head permeameter to investigate the permeability and seepage characteristics of bimrocks. The results showed that the order of factors on permeability is rock content>cementation degree>rock size>Talbot index, and permeability of bimrocks increases with the increase of rock content and decreases with the increase of clay content.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al (2017) used the constant head permeability experiment to study the seepage characteristics of bimrocks, and presented a theoretical model for the hydraulic conductivity of bimrocks. Wang et al (2021) used the constant head permeameter to investigate the permeability and seepage characteristics of bimrocks. The results showed that the order of factors on permeability is rock content>cementation degree>rock size>Talbot index, and permeability of bimrocks increases with the increase of rock content and decreases with the increase of clay content.…”
Section: Introductionmentioning
confidence: 99%